PENERAPAN MODEL PEMBELAJARAN SCRAMBLE BERBASIS WORDWALL PADA MATA PELAJARAN PPKN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Syahirudin, Muhammad (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
Civics is one of the subjects that is easily related to everyday life. PPKn is still a lesson that students consider boring, because in delivering the material the teacher only applies the lecture method without using other learning models. The aim of this research is to determine the application of the wordwall-based scrambling learning model in improving student learning outcomes in the PPKn class X Baghdad study area at SMA Plus Ass'Adah. This research uses a one group pretest posttest design, including qualitative research, with data collection techniques using observation guidelines and interview guidelines carried out using the data triangulation technique process. The subjects of this research are 23 students of Class X Baghdad. Based on the results of data analysis, it appears that there are results from the application of the wordwall-based scrambel learning model on the PPKn learning outcomes of class the average for class X Baghdad SMA Plus Ass'Adah students is 77.81%. From the research results it can be concluded that the application of the wordwall-based scrambling learning model can improve student learning outcomes.